The Cross-linguistic Relationship between English Nouns and Japanese Translations - TSUZUKU Ayako; AKAMATSU Nobuhiko (北海道英語教育学会 紀要, 2021)
The present study investigated the relationship in countability between English nouns and their Japanese translations, focusing on the judgement of noun countability between English nouns with the same Japanese translations for count and mass contexts, and those with different Japanese translations. Specifically, the study examined (1) whether or to what extent different Japanese translations for distinctive countability could help Japanese learners of English as a foreign/second language (ESL) judge their English counterparts, and (2) whether English noun countability might affect the countability judgement of Japanese nouns which have no distinction between singular and plural forms. Forty-three Japanese ESL learners were asked to judge the countability of 109 English target nouns, using a seven-point scale. Results showed positive correlations in judgement of countability between English nouns and their Japanese translations in both conditions: English nouns with the same Japanese translations for count and mass meanings, and those with different Japanese translations. These findings suggest that there are cross-linguistic relationships in noun-countability judgement between English and Japanese.